Mycobacterium abscessus Infection During Ustekinumab Treatment in Crohn's Disease: A Case Report and Review of the Literature. (31st August 2018) - Shim, Hang Hock; Cai, Sophie Carrie Shan; Chan, Webber; Low, Jenny Guek Hong; Tan, Hiok Hee; Ling, Khoon Lin
Abstract: The introduction of ustekinumab, an interleukin [IL]12/23 p40 inhibitor, to the therapeutic armamentarium of Crohn's disease has provided a much needed treatment option for patients who have failed conventional biologics with anti-tumour necrosis factor [TNF] and anti-integrin agents. Despite targeting two major cytokine pathways, the side effect profile of ustekinumab appears to be favourable in clinical trials. In particular, the risk of tuberculosis infection was observed to be lower than in patients who have received anti-TNF agents. The risk of non-tuberculosis mycobacterium infection, however, remains unknown. Here, we report the first case of a patient with Crohn's disease who developed Mycobacterium abscessus infection while on ustekinumab treatment.